Steel structure fireproof coating and preparation method thereof

By preparing the functional composite of the expandable graphite and silica solution solution, the oxygen barrier thermal protection layer is formed, which solves the problem of poor bonding performance and unstable thermal insulation efficiency of existing steel structure fire coatings. The adhesive, stable thermal insulation efficiency and good frozen resistance have significantly improved the load -bearing capacity of the steel structure in high temperature environments.

CN119371865AInactive Publication Date: 2025-01-28THE NINTH ENGINEERING CO LTD OF THE FIRST HIGHWAY ENGINEERING BUREAU OF CCCC +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411948032.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing steel structure fire-retardant coatings have poor bonding performance, unstable thermal insulation efficiency and poor refrigeration resistance, which leads to loss of load-bearing capacity in high-temperature environments and increases the risk of building collapse.

Method used

通过制备功能化复合剂,包括改性可膨胀石墨和二氧化硅溶胶,形成隔氧绝热保护层,结合膨胀绝热炭层,提高粘结性和隔热效率,并增强耐冷冻性能。

Benefits of technology

The high adhesive, stable thermal insulation efficiency, good frozen resistance and excellent fire resistance of steel structure fire coatings are realized, and the load -bearing capacity of steel structures in high temperature environments significantly improves the capacity of steel structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371865A_ABST
    Figure CN119371865A_ABST
Patent Text Reader

Abstract

The invention provides a steel structure fireproof coating and a preparation method thereof, and belongs to the technical field of fireproof coatings. The preparation method comprises the steps of preparing the functionalized complexing agent and mixing materials. The material mixing step comprises the following steps: mixing a silicone acrylic emulsion, a functional complexing agent, a flame retardant, a filler, an auxiliary agent, sepiolite fibers and deionized water, raising the temperature to 60-64 DEG C, stirring for 18-22 minutes at the stirring rotating speed of 1950-2060 rpm, and homogenizing for 4-6 minutes under the homogenizing pressure of 4.8-5.2 MPa after the stirring is finished, so as to prepare the fireproof coating after the homogenizing is finished; the fireproof coating prepared by the invention has the advantages of high bonding strength, heat exposure resistance, fire resistance, freeze-thaw cycle resistance, acid resistance, salt spray corrosion resistance and long fire endurance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fire retardant coatings, and in particular relates to a fire retardant coating for steel structures and a preparation method thereof. Background Art

[0002] Steel structure refers to a structural form that bears and transmits loads and is made of steel plates and hot-rolled, cold-bent or welded profiles connected by connectors. The steel structure system has the comprehensive advantages of light weight, factory manufacturing, quick installation, short construction period, good seismic resistance, fast investment recovery and less environmental pollution. Compared with reinforced concrete structure, it has the unique advantages of "high, large and light" in three aspects, and it is reasonably and widely used in the field of construction engineering.

[0003] However, steel structures have the disadvantage of poor fire resistance and corrosion resistance, and their mechanical strength will drop rapidly at high temperatures. In theory, when the temperature of a steel structure reaches 538°C or above under full load, it will lose static balance. Once a fire occurs in a building, the fire temperature will reach over 700°C within 10 minutes, that is, the exposed steel structure will reach its critical temperature within 10 minutes, causing plastic deformation and loss of load-bearing capacity, eventually causing the building to collapse. In order to solve the above problems, people have developed a variety of steel structure protection technologies, among which applying fire retardant coatings is the most economical and effective method.

[0004] Steel structure fire retardant coating is a functional coating that is coated on the surface of steel structure to form a fire-resistant and heat-insulating layer to change its surface combustion characteristics, delay the transfer of flame temperature to the steel structure, improve the fire resistance of the steel structure, and delay or even prevent the spread of fire.

[0005] CN11592662A discloses a corrosion-resistant, intumescent water-based fire-retardant coating for steel structures and its preparation method and application, and specifically discloses that the fire-retardant coating components include water-based hyperbranched acrylic resin, flame retardant, additive, modified filler, and water; The fire retardant coating prepared by this method has a long fire resistance period and good anti-corrosion performance, but the fire retardant coating prepared by this method has poor bonding performance, unstable thermal insulation efficiency, poor freezing resistance, and a large attenuation of thermal insulation efficiency. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a steel structure fire retardant coating and a preparation method thereof, which has good adhesion, stable thermal insulation efficiency and excellent freezing resistance.

[0007] In view of the above technical problems, the present invention adopts the following technical solutions: A method for preparing a steel structure fire retardant coating includes preparing a functionalized composite agent and mixing the materials. The specific operations are as follows: 1. Preparation of functionalized composites (1) Preparation of expandable graphite The flake graphite, potassium permanganate and sulfuric acid are mixed and subjected to ultrasonic treatment, wherein the ultrasonic time is 20-25 minutes, the ultrasonic power is 108-120W, and the ultrasonic frequency is 37-43kHz. After the ultrasonic treatment, the temperature is raised to 40-44°C, and the reaction is carried out at 40-44°C for 38-44 minutes. After the reaction is completed, the flake graphite is washed and placed at 61-65°C for drying for 4.2-4.4 hours. After the drying is completed, the flake graphite is placed in a microwave oven for expansion, wherein the microwave time is 32-36 seconds and the microwave power is 752-761W. After the microwave treatment is completed, expandable graphite is obtained. The usage ratio of the flake graphite, potassium permanganate and sulfuric acid is 9.7-10.3 g:0.8-1.2 g:20-24 mL.

[0008] (2) Preparation of modified expandable graphite The expandable graphite is placed in deionized water, and then fatty alcohol polyoxyethylene ether is added and stirred. After stirring evenly, the temperature is raised to 56-60° C. at a rate of 0.4-0.6° C. / min, 1.4-2.0 g of palmitic acid is added, and the stirring is performed. The stirring time is 1.8-2.2 h, and the stirring speed is 247-253 rpm. After the stirring is completed, the mixture is filtered and dried to obtain a modified expandable graphite; The mass ratio of the expandable graphite, deionized water, fatty alcohol polyoxyethylene ether and palmitic acid is 8.3-8.5:72-76:1.0-1.4.

[0009] (3) Preparation of silica sol Putting tetraethyl orthosilicate in N, N-dimethylformamide and stirring evenly to obtain a mixed solution 1; adding 3-aminopropyltrimethoxysilane and ammonia water to N, N-dimethylformamide and stirring evenly to obtain a mixed solution 2; adding the mixed solution 2 to the mixed solution 1 at a rate of 1.0-1.4 mL / min, and performing ultrasonic treatment after the addition is completed, the ultrasonic time is 25-30 min, the ultrasonic power is 93-98 W, and the ultrasonic frequency is 23-28 kHz. After the ultrasonic treatment is completed, stirring and reacting for 8.2-8.5 h to obtain a silica sol; The mass concentration of the ammonia water is 18-22%; In the mixed solution 1, the volume ratio of the tetraethyl orthosilicate to N,N-dimethylformamide is 21.7-22.1:186-193; In the second mixed solution, the volume ratio of N,N-dimethylformamide, 3-aminopropyltrimethoxysilane and ammonia water is 58-62:2.6-2.8:2.7-2.9; The volume ratio of the tetraethyl orthosilicate to 3-aminopropyltrimethoxysilane is 21.7-22.1:2.6-2.8.

[0010] (4) Composite The silica sol is placed in N, N-dimethylformamide, sodium dodecylbenzene sulfonate is added, and the mixture is stirred to obtain a silica solution; the modified expandable graphite is placed in N, N-dimethylformamide, and the mixture is stirred to obtain a modified expandable graphite solution; the silica solution is added dropwise to the modified expandable graphite solution at a dropping rate of 3.1-3.3 mL / min, and the mixture is stirred while adding dropwise at a speed of 122-136 rpm. After the addition is completed, the mixture is stirred and reacted for 9.8-10.2 h. After the reaction is completed, the mixture is filtered and washed, and freeze-dried at -42 to -38 ° C for 18-22 h. Finally, the mixture is ball-milled for 23-27 min, at a ball-milling speed of 104-115 rpm, and at a ball-to-material ratio of 3-5:1. After the ball-milling is completed, a functionalized composite agent is obtained; In the silica solution, the mass volume ratio of the silica sol, N,N-dimethylformamide, and sodium dodecylbenzene sulfonate is 2.4-2.6 mL:48-52 mL:0.2-0.4 g; In the modified expandable graphite solution, the mass volume ratio of the modified expandable graphite and N,N-dimethylformamide is 35-40 mg:75-80 mL; The mass volume ratio of the silica sol to the modified expandable graphite is 2.4-2.6 mL:35-40 mg.

[0011] 2. Mixing The silicone acrylic emulsion, the functional composite agent, the flame retardant, the filler, the additive, the sepiolite fiber and the deionized water are mixed, the temperature is raised to 60-64°C and stirred, the stirring speed is 1950-2060rpm, the stirring time is 18-22min, and after the stirring, homogenization is performed, the homogenization time is 4-6min, the homogenization pressure is 4.8-5.2MPa, and after the homogenization, a fire retardant coating is obtained; The mass ratio of the silicone-acrylic emulsion, the functional composite agent, the flame retardant, the filler, the additive, the sepiolite fiber, and the deionized water is 35-37:12-14:45-49:5.7-6.0:0.8-1.1:4.0-4.3:22.1-23.3; The flame retardant is a mixture of pentaerythritol and ammonium polyphosphate, and the mass ratio of pentaerythritol to ammonium polyphosphate is 1:4.5-4.9; The preparation method of the filler comprises the following steps: placing bentonite and calcium carbonate in a hydrochloric acid solution and soaking them for 1.4-1.6 hours, and drying them after the soaking to obtain a primary filler; placing the primary filler in an ethanol solution, adding tetradecyl dimethyl betaine and glyceryl monostearate, and performing ball milling treatment for 28-32 minutes, a ball milling speed of 192-207 rpm, and a ball-to-material ratio of 2-4:1, adding kH550 after the ball milling, heating the temperature to 68-72° C. for reaction for 6.3-6.7 hours, and filtering, washing, and drying them after the reaction to obtain the filler; The mass concentration of the hydrochloric acid solution is 23-27%; The mass ratio of the bentonite, calcium carbonate and hydrochloric acid solution is 14-18:8-12:234-245; The mass concentration of the ethanol solution is 46-50%; The mass ratio of the primary filler, ethanol solution, tetradecyl dimethyl betaine, glyceryl monostearate and KH550 is 18-23:146-154:1.0-1.4:1.4-1.6:1.8-2.2; The auxiliary agent is composed of polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80, and the mass ratio of the polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80 is 1.1-1.3:3.5-3.9:4.2-4.5:1.1-1.5.

[0012] A fire retardant coating for steel structures is prepared by the above preparation method.

[0013] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The present invention processes flake graphite to obtain expandable graphite, which forms an expandable heat-insulating carbon layer at high temperature, and then introduces palmitic acid for modification. The carboxyl group of palmitic acid can form a hydrogen bond with the sulfate group of expandable graphite, so that it is firmly bonded to the surface of expandable graphite; then a silica sol is prepared by a specific method, the surface of the silica sol contains amino groups, and the amino groups of the in-situ grown silica sol and the carboxyl groups of the modified expandable graphite produce hydrogen bonds, which completely coat the expandable graphite, and the silicon-oxygen bonds therein can form an oxygen-isolating heat-insulating protective layer to inhibit the thermal degradation of the base material. The silica sol The sol forms silicon dioxide at high temperature, has good heat resistance, stable properties, good heat insulation and oxygen isolation effects, and is combined with the expanded insulating carbon layer of expandable graphite with strong bonding force, so that the carbon layer density in the combustion process is high, the heat insulation efficiency is stable, the crack resistance is good, and the fire resistance is good; the present invention adopts bentonite and calcium carbonate to prepare the filler, which is ball-milled and combined with a surfactant, and then modified by silane, and the prepared filler has good compatibility with other components and high strength, and is combined with specific functional composite agents, silicone-acrylic emulsions and other components, has good adhesion, good dispersibility, and is evenly mixed, and the prepared fire retardant coating has good homogeneity, good fire resistance and stability.

[0014] 2. The fire retardant coating prepared by the present invention has a coating dry film thickness of 1.2 mm, a surface drying time of 2.8-3.1 h, and a bonding strength of 0.56-0.59 MPa.

[0015] 3. The fire retardant coating prepared by the present invention has, in terms of thermal insulation efficiency attenuation, heat resistance (960h) of 1.7-2.0%, water resistance (30h) of 0.4-0.7%, freeze-thaw cycle resistance (20 times) of 2.8-3.2%, acid resistance (480h) of 7.9-8.4%, and salt spray corrosion resistance of 3.6-4.0%.

[0016] 4. The fire retardant coating prepared by the present invention has a fire resistance limit of 185-191min. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a process flow chart for preparing the functional composite agent. DETAILED DESCRIPTION

[0018] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.

[0019] Example 1 like Figure 1 As shown, the present invention provides a method for preparing a steel structure fire retardant coating, including the steps of preparing a functionalized composite agent and mixing materials, and the specific operations are as follows: 1. Preparation of functionalized composites (1) Preparation of expandable graphite 10g of flake graphite, 1g of potassium permanganate and 22mL of sulfuric acid were mixed and ultrasonically treated for 23min, 114W of ultrasonic power and 40kHz of ultrasonic frequency. After the ultrasonic treatment, the temperature was raised to 42°C and the reaction was carried out at 42°C for 41min. After the reaction was completed, the mixture was washed and dried at 63°C for 4.3h. After the drying was completed, the mixture was expanded in a microwave oven for 34s and 758W of microwave power. After the microwave treatment was completed, expandable graphite was obtained.

[0020] (2) Preparation of modified expandable graphite 8.5 g of expandable graphite was placed in 74 g of deionized water, and then 1.2 g of fatty alcohol polyoxyethylene ether was added and stirred. After stirring evenly, the temperature was raised to 58° C. at a rate of 0.5° C. / min, 1.7 g of palmitic acid was added and stirred. The stirring time was 2.0 h and the stirring speed was 250 rpm. After the stirring was completed, the mixture was filtered and dried to obtain modified expandable graphite.

[0021] (3) Preparation of silica sol 21.9 mL of ethyl orthosilicate was placed in 190 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a mixed solution 1; 2.7 mL of 3-aminopropyltrimethoxysilane and 2.8 mL of ammonia water were added to 60 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a mixed solution 2; the mixed solution 2 was added to the mixed solution 1 at a rate of 1.2 mL / min, and after the addition was completed, ultrasonic treatment was performed, the ultrasonic time was 27 min, the ultrasonic power was 95 W, and the ultrasonic frequency was 25 kHz. After the ultrasonic treatment was completed, the reaction was stirred for 8.4 h to obtain a silica sol; The mass concentration of the ammonia water is 20%.

[0022] (4) Composite 2.5 mL of silica sol was placed in 50 mL of N, N-dimethylformamide, 0.3 g of sodium dodecylbenzene sulfonate was added, and the mixture was stirred to obtain a silica solution; 37 mg of modified expandable graphite was placed in 78 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a modified expandable graphite solution; the silica solution was added dropwise to the modified expandable graphite solution at a dropping rate of 3.2 mL / min, and the mixture was stirred while adding the silica solution at a speed of 130 rpm. After the addition was completed, the mixture was stirred for 10 hours. After the reaction was completed, the mixture was filtered and washed, and the mixture was freeze-dried at -40°C for 20 hours. Finally, the mixture was ball-milled for 25 minutes at a speed of 110 rpm and a ball-to-material ratio of 4:1. After the ball milling was completed, a functional composite was obtained.

[0023] 2. Mixing 36g of silicone acrylic emulsion, 13g of functional composite agent, 47g of flame retardant, 5.8g of filler, 1.0g of auxiliary agent, 4.2g of sepiolite fiber and 22.8g of water were mixed, the temperature was raised to 62°C for stirring, the stirring speed was 2000rpm, the stirring time was 20min, and after the stirring was completed, homogenization was performed, the homogenization time was 5min, the homogenization pressure was 5.0MPa, and after the homogenization was completed, a fire retardant coating was obtained; The flame retardant is a mixture of pentaerythritol and ammonium polyphosphate, and the mass ratio of pentaerythritol to ammonium polyphosphate is 1:4.7; The preparation method of the filler comprises the following steps: placing 16g of bentonite and 10g of calcium carbonate in a 240g hydrochloric acid solution for immersion for 1.5h, and drying to obtain a primary filler; placing 21g of the primary filler in a 150g ethanol solution, adding 1.2g of tetradecyl dimethyl betaine and 1.5g of glyceryl monostearate, and performing ball milling for 30min at a ball milling speed of 200rpm and a ball-to-material ratio of 3:1; adding 2.0g of kH550 after the ball milling, heating to 70°C for reaction for 6.5h, and filtering, washing, and drying to obtain a filler; The mass concentration of the hydrochloric acid solution is 25%; The mass concentration of the ethanol solution is 48%; The auxiliary agent is composed of polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80, and the mass ratio of the polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80 is 1.2:3.7:4.3:1.3.

[0024] Example 2 1. Preparation of functionalized composites (1) Preparation of expandable graphite 9.7 g of flake graphite, 0.8 g of potassium permanganate and 20 mL of sulfuric acid were mixed and ultrasonically treated for 20 min, with an ultrasonic power of 108 W and an ultrasonic frequency of 37 kHz. After the ultrasonic treatment, the mixture was heated to 40°C and reacted at 40°C for 38 min. After the reaction, the mixture was washed and dried at 61°C for 4.2 h. After the drying, the mixture was expanded in a microwave oven for 32 s and a microwave power of 752 W. After the microwave treatment, expandable graphite was obtained.

[0025] (2) Preparation of modified expandable graphite 8.3 g of expandable graphite was placed in 72 g of deionized water, and then 1.0 g of fatty alcohol polyoxyethylene ether was added and stirred. After stirring evenly, the temperature was raised to 56° C. at a rate of 0.4° C. / min, 1.4 g of palmitic acid was added and stirred. The stirring time was 1.8 h and the stirring speed was 247 rpm. After the stirring was completed, the mixture was filtered and dried to obtain modified expandable graphite.

[0026] (3) Preparation of silica sol 21.7 mL of tetraethyl orthosilicate was placed in 186 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a mixed solution 1; 2.6 mL of 3-aminopropyltrimethoxysilane and 2.7 mL of ammonia water were added to 58 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a mixed solution 2; the mixed solution 2 was added to the mixed solution 1 at a rate of 1.0 mL / min, and after the addition was completed, ultrasonic treatment was performed, the ultrasonic time was 25 min, the ultrasonic power was 93 W, and the ultrasonic frequency was 23 kHz. After the ultrasonic treatment was completed, the reaction was stirred for 8.2 h to obtain a silica sol; The mass concentration of the ammonia water is 18%.

[0027] (4) Composite 2.4 mL of silica sol was placed in 48 mL of N, N-dimethylformamide, 0.2 g of sodium dodecylbenzene sulfonate was added, and the mixture was stirred to obtain a silica solution; 35 mg of modified expandable graphite was placed in 75 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a modified expandable graphite solution; the silica solution was added dropwise to the modified expandable graphite solution at a dropping rate of 3.1 mL / min, and the mixture was stirred while adding dropwise at a speed of 122 rpm. After the addition was completed, the mixture was stirred and reacted for 9.8 h. After the reaction was completed, the mixture was filtered and washed, and freeze-dried at -42°C for 18 h. Finally, the mixture was ball-milled for 23 min, at a speed of 104 rpm, and at a ball-to-material ratio of 3:1. After the ball milling was completed, a functionalized composite was obtained.

[0028] 2. Mixing 35g of silicone acrylic emulsion, 12g of functional composite agent, 45g of flame retardant, 5.7g of filler, 0.8g of additive, 4.0g of sepiolite fiber and 22.1g of water were mixed, the temperature was raised to 60°C for stirring, the stirring speed was 1950rpm, the stirring time was 18min, and homogenization was performed after the stirring, the homogenization time was 4min, the homogenization pressure was 4.8MPa, and after the homogenization, a fire retardant coating was obtained; The flame retardant is a mixture of pentaerythritol and ammonium polyphosphate, and the mass ratio of pentaerythritol to ammonium polyphosphate is 1:4.5; The preparation method of the filler is as follows: 14g of bentonite and 8g of calcium carbonate are soaked in a 234g hydrochloric acid solution for 1.4h, and after the soaking, the primary filler is dried to obtain the primary filler; 18g of the primary filler is placed in a 146g ethanol solution, 1.0g of tetradecyl dimethyl betaine and 1.4g of glyceryl monostearate are added, and the ball milling treatment is performed for 28min, the ball milling speed is 192rpm, and the ball-to-material ratio is 2:1. After the ball milling, 1.8g of kH550 is added, the temperature is raised to 68°C for reaction, and the reaction time is 6.3h. After the reaction is completed, the filler is filtered, washed, and dried to obtain the filler; The mass concentration of the hydrochloric acid solution is 23%; The mass concentration of the ethanol solution is 46%; The auxiliary agent is composed of polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80, and the mass ratio of the polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80 is 1.1:3.5:4.2:1.1.

[0029] Example 3 1. Preparation of functionalized composites (1) Preparation of expandable graphite 10.3 g of flake graphite, 1.2 g of potassium permanganate and 24 mL of sulfuric acid were mixed and ultrasonically treated for 25 min, 120 W of ultrasonic power and 43 kHz of ultrasonic frequency. After the ultrasonic treatment, the temperature was raised to 44 °C and the reaction was carried out at 44 °C for 44 min. After the reaction was completed, the mixture was washed and dried at 65 °C for 4.4 h. After the drying was completed, the mixture was expanded in a microwave oven for 36 s and 761 W of microwave power. After the microwave treatment was completed, expandable graphite was obtained.

[0030] (2) Preparation of modified expandable graphite 8.7 g of expandable graphite was placed in 76 g of deionized water, and then 1.4 g of fatty alcohol polyoxyethylene ether was added and stirred. After stirring evenly, the temperature was raised to 60°C at a rate of 0.6°C / min, 2.0 g of palmitic acid was added and stirred. The stirring time was 2.2 h and the stirring speed was 253 rpm. After the stirring was completed, the mixture was filtered and dried to obtain modified expandable graphite.

[0031] (3) Preparation of silica sol 22.1 mL of ethyl orthosilicate was placed in 193 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a mixed solution 1; 2.8 mL of 3-aminopropyltrimethoxysilane and 2.9 mL of ammonia water were added to 62 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a mixed solution 2; the mixed solution 2 was added to the mixed solution 1 at a rate of 1.4 mL / min, and after the addition was completed, ultrasonic treatment was performed, the ultrasonic time was 30 min, the ultrasonic power was 98 W, and the ultrasonic frequency was 28 kHz. After the ultrasonic treatment was completed, the reaction was stirred for 8.5 h to obtain a silica sol; The mass concentration of the ammonia water is 22%.

[0032] (4) Composite 2.6 mL of silica sol was placed in 52 mL of N, N-dimethylformamide, 0.4 g of sodium dodecylbenzene sulfonate was added, and the mixture was stirred to obtain a silica solution; 40 mg of modified expandable graphite was placed in 80 mL of N, N-dimethylformamide, and the mixture was stirred to obtain a modified expandable graphite solution; the silica solution was added dropwise to the modified expandable graphite solution at a dropping rate of 3.3 mL / min, and the mixture was stirred while adding dropwise at a speed of 136 rpm. After the addition was completed, the mixture was stirred and reacted for 10.2 h. After the reaction was completed, the mixture was filtered and washed, and freeze-dried at -38°C for 22 h. Finally, the mixture was ball-milled for 27 min, at a speed of 115 rpm, and at a ball-to-material ratio of 5:1. After the ball milling was completed, a functionalized composite was obtained.

[0033] 2. Mixing 37g of silicone acrylic emulsion, 14g of functional composite agent, 49g of flame retardant, 6.0g of filler, 1.1g of additive, 4.3g of sepiolite fiber and 23.3g of water were mixed, the temperature was raised to 64°C for stirring, the stirring speed was 2060rpm, the stirring time was 22min, and homogenization was performed after the stirring, the homogenization time was 6min, the homogenization pressure was 5.2MPa, and after the homogenization, a fire retardant coating was obtained; The flame retardant is a mixture of pentaerythritol and ammonium polyphosphate, and the mass ratio of pentaerythritol to ammonium polyphosphate is 1:4.9; The preparation method of the filler is as follows: 18g of bentonite and 12g of calcium carbonate are soaked in a 245g hydrochloric acid solution for 1.6h, and after the soaking, the primary filler is dried to obtain the primary filler; 23g of the primary filler is placed in a 154g ethanol solution, 1.4g of tetradecyl dimethyl betaine and 1.6g of glyceryl monostearate are added, and ball milling is performed for 32min, the ball milling speed is 207rpm, and the ball-to-material ratio is 4:1. After the ball milling, 2.2g of kH550 is added, the temperature is raised to 72°C for reaction, and the reaction time is 6.7h. After the reaction is completed, the filler is filtered, washed, and dried to obtain the filler; The mass concentration of the hydrochloric acid solution is 27%; The mass concentration of the ethanol solution is 50%; The auxiliary agent is composed of polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80, and the mass ratio of the polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80 is 1.3:3.9:4.5:1.5.

[0034] Comparative Example 1 Based on Example 1, the changes are as follows: In the step of preparing the functionalized composite agent, the step of modifying expandable graphite is omitted; In the step of preparing silica sol, 3-aminopropyltrimethoxysilane is replaced by an equal amount of N,N-dimethylformamide; In the compounding step, an equal amount of sodium dodecylbenzene sulfonate is replaced by N,N-dimethylformamide, and an equal amount of modified expandable graphite is replaced by expandable graphite; The rest of the operations are the same.

[0035] Comparative Example 2 Based on Example 1, the changes are as follows: In the compounding step, the filler is replaced by the primary filler in equal amounts; The rest of the operations are the same.

[0036] Performance Testing Q235 steel was used as the test substrate. The size of the test substrate was 150×70×6 mm. Rust was removed from the test substrate and anti-rust primer was sprayed with a thickness of 50 μm. After the anti-rust primer was touch-dried, the fire retardant coatings prepared in Examples 1-3 and Comparative Examples 1-2 were applied respectively until the coating dry film thickness was 1.2 mm. Performance tests were then performed, wherein moisture and heat resistance, water resistance, freeze-thaw cycle resistance, acid resistance, and salt spray corrosion resistance were all recorded as insulation efficiency attenuation. The specific results are as follows: Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Dry time h 2.8 3.1 3.0 4.5 4.1 Bond strength MPa 0.59 0.56 0.58 0.35 0.40 Heat exposure resistance (960h)% 1.7 2.0 1.8 3.9 3.4 Water resistance (30h)% 0.4 0.7 0.6 2.7 2.3 Freeze-thaw cycle resistance (20 times)% 2.8 3.2 2.9 5.3 4.7 Acid resistance (480h)% 7.9 8.4 8.2 12.6 10.9 Salt spray corrosion resistance (35 times)% 3.6 4.0 3.9 7.1 6.2 Fire resistance limit min 191 185 187 142 148 The invention processes flake graphite to obtain expandable graphite, which forms an expandable heat-insulating carbon layer at high temperature, and then introduces palmitic acid for modification, wherein the carboxyl group of the palmitic acid can form a hydrogen bond with the sulfate group of the expandable graphite, so that the palmitic acid is firmly bonded to the surface of the expandable graphite; and then a silica sol is prepared by a specific method, wherein the surface of the silica sol contains amino groups, and the amino groups of the in-situ grown silica sol generate a hydrogen bond with the carboxyl groups of the modified expandable graphite, so that the expandable graphite is completely coated, and the silicon-oxygen bonds and the like therein can form an oxygen-isolating heat-insulating protective layer, so as to inhibit the thermal degradation of the base material, and the silica sol Silicon dioxide is formed at high temperature, has good heat resistance, stable properties, and good heat insulation and oxygen isolation effects. It is combined with the expanded insulating carbon layer of expandable graphite with strong bonding force, so that the carbon layer density during the combustion process is high, the heat insulation efficiency is stable, the crack resistance is good, and the fire resistance is good. The present invention adopts bentonite and calcium carbonate to prepare the filler, which is ball-milled and combined with a surfactant, and then modified by silane. The prepared filler has good compatibility with other ingredients and high strength. It is combined with specific functional composite agents, silicone-acrylic emulsions and other ingredients, has good adhesion, good dispersibility, and is evenly mixed. The prepared fire retardant coating has good homogeneity, good and stable fire resistance.

[0037] In Comparative Example 1, in the step of preparing the functionalized composite agent, the modification step of the expandable graphite is omitted, and the expandable graphite obtained has strong agglomeration force and poor dispersibility. In addition, the step of preparing the silica sol is omitted, and sodium dodecylbenzene cyclopentane is omitted in the composite step, resulting in poor coating of the silica sol for the soluble expandable graphite, weak bonding force, and poor dispersibility, which in turn affects the compatibility with other ingredients and ultimately affects the homogeneity of the fire retardant coating, resulting in poor stability and poor fire resistance of the fire retardant coating.

[0038] In Comparative Example 2, in the mixing step, the filler is replaced by the primary filler in equal amount. The primary filler has poor dispersibility and poor compatibility with other ingredients. The homogeneity of the prepared coating is poor, which affects the comprehensive performance of the fire retardant coating.

[0039] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.

[0040] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fire retardant coating for a steel structure, characterized in that: The preparation method comprises the steps of preparing a functionalized composite agent and mixing materials; The preparation of the functionalized composite agent includes the steps of preparing expandable graphite, preparing modified expandable graphite, preparing silica sol and compounding; The step of preparing the modified expandable graphite is as follows: placing the expandable graphite in deionized water, then adding fatty alcohol polyoxyethylene ether and stirring, after stirring evenly, heating to 56-60° C. at a rate of 0.4-0.6° C. / min, adding 1.4-2.0 g of palmitic acid, stirring, the stirring time is 1.8-2.2 h, the stirring speed is 247-253 rpm, after the stirring is completed, filtering and drying, and obtaining the modified expandable graphite; The steps of preparing the silica sol are as follows: placing tetraethyl orthosilicate in N,N-dimethylformamide, stirring evenly, and obtaining a mixed solution 1; adding 3-aminopropyltrimethoxysilane and ammonia water to N,N-dimethylformamide, stirring evenly, and obtaining a mixed solution 2; adding the mixed solution 2 to the mixed solution 1 at a rate of 1.0-1.4 mL / min, and performing ultrasonic treatment after the addition is completed, the ultrasonic time is 25-30 min, the ultrasonic power is 93-98 W, the ultrasonic frequency is 23-28 kHz, and after the ultrasonic treatment is completed, stirring and reacting for 8.2-8.5 h to obtain the silica sol; The compounding step is as follows: placing silica sol in N, N-dimethylformamide, adding sodium dodecylbenzene sulfonate, and stirring to obtain a silica solution; placing modified expandable graphite in N, N-dimethylformamide, and stirring to obtain a modified expandable graphite solution; dropping the silica solution into the modified expandable graphite solution at a dropping rate of 3.1-3.3 mL / min, stirring while dropping, and the stirring speed is 122-136 rpm. After the dropping is completed, stirring and reacting are continued for 9.8-10.2 hours. After the reaction is completed, filtering and washing, placing at -42 to -38°C for freeze drying for 18-22 hours, and finally ball milling, the ball milling time is 23-27 minutes, the ball milling speed is 104-115 rpm, and the ball-to-material ratio is 3-5:

1. After the ball milling is completed, a functionalized composite agent is obtained; The mixing step comprises mixing silicone acrylic emulsion, functional composite agent, flame retardant, filler, additive, sepiolite fiber and deionized water, raising the temperature to 60-64° C. for stirring, the stirring speed is 1950-2060 rpm, the stirring time is 18-22 min, and after the stirring, homogenizing is performed, the homogenizing time is 4-6 min, the homogenizing pressure is 4.8-5.2 MPa, and after the homogenization, a fire retardant coating is obtained; The preparation method of the filler comprises the following steps: placing bentonite and calcium carbonate in a hydrochloric acid solution and soaking them for 1.4-1.6 hours, and drying them to obtain a primary filler after the soaking; placing the primary filler in an ethanol solution, adding tetradecyl dimethyl betaine and glyceryl monostearate, and performing ball milling treatment for 28-32 minutes, a ball milling speed of 192-207 rpm, and a ball-to-material ratio of 2-4:1, adding kH550 after the ball milling, heating the temperature to 68-72°C for reaction, and the reaction time is 6.3-6.7 hours, and filtering, washing, and drying after the reaction to obtain the filler.

2. The method for preparing a fire retardant coating for steel structure according to claim 1, characterized in that: The step of preparing expandable graphite is: mixing flake graphite, potassium permanganate and sulfuric acid, performing ultrasonic treatment, the ultrasonic time is 20-25 minutes, the ultrasonic power is 108-120W, the ultrasonic frequency is 37-43kHz, after the ultrasonic treatment, heating to 40-44°C, reacting at 40-44°C for 38-44 minutes, after the reaction, washing, placing at 61-65°C for drying for 4.2-4.4 hours, placing in a microwave oven for expansion after the drying, the microwave time is 32-36 seconds, the microwave power is 752-761W, after the microwave treatment, the expandable graphite is obtained; The usage ratio of the flake graphite, potassium permanganate and sulfuric acid is 9.7-10.3 g:0.8-1.2 g:20-24 mL.

3. The method for preparing a fire retardant coating for steel structure according to claim 1, characterized in that: In the step of preparing modified expandable graphite, the mass ratio of the expandable graphite, deionized water, fatty alcohol polyoxyethylene ether and palmitic acid is 8.3-8.5:72-76:1.0-1.

4.

4. The method for preparing a fire retardant coating for steel structure according to claim 1, characterized in that: In the step of preparing the silica sol, the mass concentration of the ammonia water is 18-22%; In the mixed solution 1, the volume ratio of the tetraethyl orthosilicate to N,N-dimethylformamide is 21.7-22.1:186-193; In the mixed solution 2, the volume ratio of N,N-dimethylformamide, 3-aminopropyltrimethoxysilane and ammonia water is 58-62: 2.6-2.8:2.7-2.9。 5. The method for preparing a fire retardant coating for steel structure according to claim 4, characterized in that: The volume ratio of the tetraethyl orthosilicate to 3-aminopropyltrimethoxysilane is 21.7-22.1:2.6-2.

8.

6. The method for preparing a fire retardant coating for steel structure according to claim 1, characterized in that: In the compounding step, in the silica solution, the mass volume ratio of the silica sol, N,N-dimethylformamide, and sodium dodecylbenzene sulfonate is 2.4-2.6 mL:48-52 mL:0.2-0.4 g.

7. The method for preparing a fire retardant coating for steel structure according to claim 1, characterized in that: In the modified expandable graphite solution, the mass volume ratio of the modified expandable graphite and N,N-dimethylformamide is 35-40 mg:75-80 mL; The mass volume ratio of the silica sol to the modified expandable graphite is 2.4-2.6 mL:35-40 mg.

8. The method for preparing a fire retardant coating for steel structure according to claim 1, characterized in that: In the mixing step, the mass ratio of the silicone acrylic emulsion, the functional composite agent, the flame retardant, the filler, the additive, the sepiolite fiber, and the deionized water is 35-37:12-14:45-49:5.7-6.0:0.8-1.1:4.0-4.3:22.1-23.3; The flame retardant is a mixture of pentaerythritol and ammonium polyphosphate, and the mass ratio of pentaerythritol to ammonium polyphosphate is 1:4.5-4.9; The auxiliary agent is composed of polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80, and the mass ratio of the polyacrylic acid, dodecyl alcohol ester, hydroxypropyl methylcellulose and Tween 80 is 1.1-1.3:3.5-3.9:4.2-4.5:1.1-1.

5.

9. The method for preparing a fire retardant coating for steel structure according to claim 1, characterized in that: The preparation method of the filler, wherein the mass concentration of the hydrochloric acid solution is 23-27%; The mass ratio of the bentonite, calcium carbonate and hydrochloric acid solution is 14-18:8-12:234-245; The mass concentration of the ethanol solution is 46-50%; The mass ratio of the primary filler, the ethanol solution, myristyl dimethyl betaine, glyceryl monostearate and KH550 is 18-23:146-154:1.0-1.4:1.4-1.6:1.8-2.

2.

10. A fire retardant coating for steel structures prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Aqueous ultra-thin expansion type steel structure fire-proof anti-corrosive paint and preparation method thereof

    CN101857760A

  • Preparation method of organic matter carbonized composite silicon carbon negative electrode by taking silica sol as silicon source

    CN107359317A

  • Preparation methods of SiO2 nano particle modified expandable graphite and flame retardant polypropylene

    CN108410066A

  • Waterborne fireproof coating for ultrathin expanded steel structure and preparation method thereof

    CN109439083A

  • Preparation method and application of expanded graphite with preferential adsorption performance on aromatic compounds

    CN111620335A